The Consequences of Egg Adaptation in the H3N2 Component to the Immunogenicity of Live Attenuated Influenza Vaccine - Goldhill,DH; Lindsey,B; Kugathasan,R; Garza,ZF; Jagne,YJ; Sallah,HJ; Goderski,G; van,Tol S; Höschler,K; Meijer,A; Barclay,WS; de,Silva TI (2019)
Abstract Adaptation in egg-passaged vaccine strains may cause reduced vaccine effectiveness due to altered antigenicity of the influenza haemagglutinin. We tested whether egg adaptation modified serum and mucosal antibody responses to the A(H3N2) component in the Live Attenuated Influenza Vaccine (LAIV). Twice as many children seroconverted to an egg-adapted H3N2 than the equivalent wildtype strain. Seroconversion to the wildtype strain was greater in children seronegative pre-LAIV, whereas higher mucosal IgA responses to wildtype antigen were observed if seropositive prior to vaccination. Sequencing of virus from nasopharyngeal swabs from 7 days post-LAIV showed low sequence diversity and no reversion of egg-adaptive mutations.